O ensino de língua inglesa em HQ: possibilidade de um ensino significativo com a ferramenta digital TOONDOO - Silva, Patrícia Santos da (2015)
Using technology is still a great challenge to many teachers in their work development. Questions and reflections about what are the real education power of technology to the teaching/learning process and how they can influence the pedagogical actions are present on educacional research. This way, this work has as objective evaluate the use of a digital tool of cartoon production, the TOONDOO, in English language teaching, as this textual genre (HQs) stimulates reading, writing and its production process which involv criativity in elabaration of settings and characters which should be associated to verbal and non-verbal texts, promoting a relation to the object of studying, stimulating the imagination in knowledge acquisition. The research was developed with 20 students of 6th and 7th of a public high school in Recife. It’s a research-in-action, once it plans the improvement of a practice, it aplies, observes and describes the action effects, and evaluated the results. Among the teorical references are Moran (2013), Vergueiro (2009), Xavier (2007) and others. We hope that the results of this study stimulates other profissionals of educacional area to use technology and HQs as a tool in their teaching/learning process of foreign language and other subjects.